Structural and ultrastructural evidence for telocytes in prostate stroma - Corradi, Lara S. [UNESP] (2013)
The prostate comprises a glandular epithelium embedded within a fibromuscular stroma. The stroma is a complex arrangement of cells and extracellular matrix (ECM) components in addition to growth factors, regulatory molecules, remodelling enzymes, blood vessels, nerves and immune cells. The principal sources of ECM components are fibroblasts and smooth muscle cells (SMC), which synthesize the structural and regulatory components of the ECM. Telocytes (TCs) were recently described as a novel stromal cell type that exhibited characteristic features. The aim of this study was to confirm the presence of TCs in prostate stromal tissue of gerbils, as the stromal compartment of this gland is a dynamic microenvironment. We used transmission electron microscopy (TEM), light microscopy and immunohistochemistry methods to provide morphological evidence for the presence of TCs. Cells that resembled TCs were observed in gerbil prostatic stroma. These cells had small cellular bodies with very thin and extremely long cellular processes. They were found primarily in the subepithelial area and also at the periphery of SMC layers. TCs also exhibited moniliform processes, caveolae and nuclei surrounded by small amounts of cytoplasm. Close contacts between TC podomers were evident, particularly in the adjacent epithelial compartment. This morphological evidence supported the presence of TCs in the gerbil prostatic stroma, which we report for the first time. © 2013 The Authors. Published by Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.